Resistiendo al Covid-19 y levantando las voces desde el encierro: análisis de cartas públicas de mujeres recluidas en prisiones de Lima, Perú = Resisting COVID-19 and raising voices from behind prison walls : analysis of public letters from women in prison in Lima, Peru - Bracco Bruce, Lucia (Oñati Socio-Legal Series, 2022)
Over the last few decades, an exponential increase in the prison population highlights the punitive turn that has led to a crisis in the penitentiary system and makes prisoners a vulnerable group for health emergencies such as the COVID-19. In Latin America, this vulnerability increases due to overcrowding and precarious living conditions inside prisons. This paper recovers silenced voices within the prison system. From a qualitative methodology, we analyze the claim actions of women prisoners at a prison in Lima-Peru during the first months of COVID-19. We identify that women deprived of their liberty position themselves to claim the State's abandonment from three self-identifying axes: 1. The sense of collectivity; 2. The resocialization process framed in the logic of prison categorization; and 3. Their role as reproducers of care. It is concluded that these are strategies for the deployment of agency and proactive actions of imprisoned women.